Pandemic Effects in the Influence of Growth of Credit, CAR, LDR and Credit Interest on NPL on Commercial Banks in Indonesia - Rahmatullah Rahmatullah; Matrodji Mustafa (Budapest International Research and Critics University, 2022)
This study aims to analyze the effect of credit growth, adequate capital ratio (CAR), loan to deposit ratio (LDR), credit interest and the impact of the COVID-19 pandemic on Non-Performing Loans (NPL) at commercial banks in Indonesia. The population of this study is all banks in Indonesia, amounting to 120 in 2014 to 107 in 2021. The data analysis method uses multiple linear regression analysis. The results of the study found that credit growth, Capital Adequacy Ratio (CAR), Loan-to-Deposit Ratio (LDR), credit interest and the pandemic effect had a partial effect on Non-Performing Loans (NPL), namely CAR, LDR and the pandemic effect had a significant effect while credit growth and loan interest had no significant effect. The increase in CAR, LDR and the pandemic makes NPL also increase. The implications of this research are discussed in the article.